Profil Kimiawi Makanan Pendamping asi dengan Pemanfaatan Pati Ubi Jalar Ungu Metode Modifikasi Ultrasonikasi - Ira Gusti Riani; Nia Boru Ritonga; Ahlam Inayatullah; Marta Tika Handayani (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Negeri Tanah Laut, 2023)
Weaning food is given as a complement to breast milk which is helpful for babies in the process of baby led weaning. At six months, the baby's digestive tract is able to digest some food such as flour so baby can be introduced to solid food. Purple sweet potato has good nutrition such as carbohydrates, protein, fat, vitamins, minerals, and water. Ultrasound modification is considered easier, simpler, and safer because it does not use chemical additives. This research used a non-factorial completely randomized design (CRD) with one variable treatment and three replication. The variable was the ratio of sweet potato ultrasound modified starch and rice flour (0%:100%; 20%:80%; 40%:60%; 60%:40%; 80%:20%; 100%:0%). The result showed the ratio of sweet potato ultrasound modified starch and rice flour had significant effect on the chemical properties of instant weaning food. The significant result was shown by formulation of sweet potato ultrasound modified starch 100% and rice flour 0% with moisture content 3.88%, ash 0.69%, protein 16.87%, fat 1.66%, and carbohydrates 76.88%.